Population genetic structure and colonization sequence of Drosophila subobscura in the Canaries and Madeira Atlantic islands as inferred by autosomal, sex-linked and mtDNA traits - Pinto, F. M. (2022)
The genetic structure In Atlantic Islands and continental populations of Drosophila subobscura has been studied using autosomal and sex-linked allozymes and ml tochondrial DNA (mtDNA) haplotypes. From the data it Is deduced that whereas the Canary Islands have long been isolated, the neighboring island of Madeira has been subjected to continuous migration from the mainland. In addition, sex-linked allo zymes and mtDNA data show a large divergence between the geologically younger western Islands of the Canarian Archipelago and the older central ones, finding strong founder effects In the former. Divergence rates of sex-linked and mltochon drlal genes relative to autosomlc loci several times higher than expected under neutrality have been explained by differential migration between sexes. The Ca narian Archipelago colonization fits in well with a stepping-stone model of a direc tional east-west migration that parallels the geological origin of these Islands.